1985
DOI: 10.1902/jop.1985.56.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Studies of One Family Manifesting Rapidly Progressive, Juvenile and Prepubertal Periodontitis

Abstract: We report clinical, radiographic and historical data on a large family with an unusually high prevalence of periodontitis. The proband, a 20‐year‐old black male, had the classic features of juvenile periodontitis (JP). His father was periodontally normal, while his mother had lost all her teeth at age 27 because of rapidly progressive periodontitis (RP). In addition to the 13 living children the couple had had 2 miscarriages. Of the children, one had RP, five had JP and two had prepubertal periodontitis (PP). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
54
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 34 publications
4
54
0
Order By: Relevance
“…Cumulative studies in the literature and the results reported in our patient show that prepubertal and juvenile periodontitis do not necessarily occur in "otherwise healthy adolescence", as described by Baer (1971) and Page et al, (1983). Most of the patients described in the literature have abnormal neutrophil and monocyte functions (Pritchard et al 1984, Vandesteen et al 1984, Spektor et al, 1985 and are usually suffering from upper respiratory tract infections and otitis media at a fairly early age. In the case presented, the estimated age at which the disease started is 7 or 8 years.…”
Section: Discussionsupporting
confidence: 51%
“…Cumulative studies in the literature and the results reported in our patient show that prepubertal and juvenile periodontitis do not necessarily occur in "otherwise healthy adolescence", as described by Baer (1971) and Page et al, (1983). Most of the patients described in the literature have abnormal neutrophil and monocyte functions (Pritchard et al 1984, Vandesteen et al 1984, Spektor et al, 1985 and are usually suffering from upper respiratory tract infections and otitis media at a fairly early age. In the case presented, the estimated age at which the disease started is 7 or 8 years.…”
Section: Discussionsupporting
confidence: 51%
“…Marazita et al (1994), in their (predominantly black) North‐American population, found around 50% of examined relatives of EOP patients to be affected with the same condition. Other studies presented even higher percentages of affected relatives, but these were either examined relatives of only a group of selected families which presented already with at least one or more relatives affected (Hart et al 1991, 1993), or described specific families, which presented an exceptionally high number of affected family members (Spektor et al 1985, Hodge et al 2000, Trevilatto et al 2002). Therefore, they do not represent percentage figures of a random population.…”
Section: Discussionmentioning
confidence: 99%
“…Destructive periodontal disease affectmg the deciduous dentition has otily been described in a few isolated case reports. (Page et al 1983, Spector et al 1985, Page et al 1985. While there is some evidence for a genetic component to adult periodontitis, a form of early onset periodontitis.…”
mentioning
confidence: 99%